Torsion of a rectangular bar: Complex phase distribution in 304L steel revealed by neutron tomography. (October 2022) - Tran, Khanh Van; Woracek, Robin; Kardjilov, Nikolay; Markötter, Henning; Abou-Ras, Daniel; Puplampu, Stephen; Förster, Christiane; Penumadu, Dayakar; Dahlberg, Carl F.O.; Banhart, John; Manke, Ingo
Graphical abstract: Highlights: Neutron imaging reveals phase transformation behavior of metastable austenitic stainless steels under plastic deformation. 3D mapping of phase distributions in polycrystalline materials non-destructively. In-situ investigation of the effect of a geometrical factor on phase transformation in a rectangular TRIP steel sample under torsion load. New non-destructive spectroscopic technique based on neutron diffraction contrast is eligible for study of material phase. Abstract: Metastable austenitic stainless steel (304L) samples with a rectangular cross-section were plastically deformed in torsion during which they experienced multiaxial stresses that led to a complex martensitic phase distribution owing to the transformation induced plasticity effect. A three-dimensional characterization of the phase distributions in these cm-sized samples was carried out by wavelength-selective neutron tomography. It was found that quantitatively correct results are obtained as long as the samples do not exhibit any considerable preferential grain orientation. Optical microscopy, electron backscatter diffraction, and finite element modeling were used to verify and explain the results obtained by neutron tomography. Altogether, neutron tomography was shown to extend the range of microstructure characterization methods towards the meso- and macroscale.